The role of brand trust as a mediator in the relationship between brand satisfaction and purchase intention - Cuong, Dam Tri (International Journal of Psychosocial Rehabilitation, 2020)
The present purpose of this study was to empirical research on the role of brand trust as a mediator in the connection between brand satisfaction and purchase intention. We tested research data from 255 customers at laptop shops in Ho Chi Minh, Vietnam. PLS - Partial Least Squares was implemented to evaluate the measurement model and the structural model. The result of the investigation explained that brand satisfaction had a positive impact on brand trust and purchase intention. The findings also revealed that brand trust had a positive influence on purchase intention. Furthermore, the results also disclosed that brand trust had a mediator variable in the relationship between brand satisfaction and purchase intention.